Chemoselective reaction of bifunctional carboxysulfonic acid systems: Preparation of useful intermediates for chemiluminescent, fluorescent and UV absorbing bifunctional linkers. Issue 40 (1st October 2020) - Haack, Richard A.; Hershberger, Stefan J.; Best, Quinn A.; Swift, Kerry M.; Tetin, Sergey Y.
Graphical abstract: Heterobifunctional compounds are of considerable interest in convergent synthesis strategies as well as in the labeling/tagging of biological molecules. Herein is described a synthetic strategy to functionalize sulfonic acids in the presence of carboxylic acids without the need for protection/deprotection steps. Bifunctional carboxysulfonic acids are transformed under mild conditions to the corresponding carboxysulfonyl fluorides which are reacted with the amine of choice to provide sulfonamides. The carboxylic acid remains free and is available for subsequent activation and further chemical elaboration. The generality of this approach is demonstrated herein, and an example of utility is outlined in which carboxysulfonyl-containing chemiluminescent reagents are transformed into unique red-shifted chemiluminescent reagents. Highlights: Sulfonyl fluorides were prepared in the presence of carboxylic acids in high yield. Selective functionalization of sulfonic acids without protection/deprotection steps. Sulfonyl fluorides were shown to be useful for producing bifunctional linkers. Heterobifunctional chemiluminescent and fluorescent sulfonyl fluorides were produced. Chemiluminescent reagents linked to a fluorophore produced red-shifted emission. Abstract: Heterobifunctional compounds are of considerable interest in convergent synthesis strategies as well as in the labeling/tagging of biological molecules. Herein is described a synthetic strategy to functionalize sulfonic acids in the presence of carboxylic acids without the need for protection/deprotection steps. Bifunctional carboxysulfonic acids are transformed under mild conditions to the corresponding carboxysulfonyl fluorides which are reacted with the amine of choice to provide sulfonamides. The carboxylic acid remains free and is available for subsequent activation and further chemical elaboration. The generality of this approach is demonstrated herein, and an example of utility is outlined in which carboxysulfonyl-containing chemiluminescent reagents are transformed into unique red-shifted chemiluminescent reagents.